2017
DOI: 10.4236/jpee.2017.512009
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Prediction of Tip Vortices from Tandem Propellers in the Counter-Rotating Type Tidal Stream Power Unit

Abstract: Ocean energy has a potential of providing a large amount of renewable energy around the world. One of the forms of ocean energy, tidal stream power is widely recognized as the continuous, predictable and eco-friendly ocean energy source. Unique tandem propellers that can counter-rotate have been designed to generate electric power effectively from a tidal stream. This type of power unit has several advantages compare to the conventional unit with a single propeller. At the design of the tidal stream power unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The authors in their works emphasize the importance and necessity of studying hub losses, but such results are not presented in the works. In [18], the results of studies of the contra rotating tandem propellers are shown, where it is shown that such a scheme makes it possible to completely eliminate the hub vortex and losses due to the untwisting of the hub vortex from the first row of blades in the second row, but this approach is unacceptable for tandem propellers with joined blades since they rotate together with one peripheral velocity. To reduce hub losses, it was proposed in [19,20] to use active and passive methods for controlling separated flows on the aerodynamic surfaces of the blades.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The authors in their works emphasize the importance and necessity of studying hub losses, but such results are not presented in the works. In [18], the results of studies of the contra rotating tandem propellers are shown, where it is shown that such a scheme makes it possible to completely eliminate the hub vortex and losses due to the untwisting of the hub vortex from the first row of blades in the second row, but this approach is unacceptable for tandem propellers with joined blades since they rotate together with one peripheral velocity. To reduce hub losses, it was proposed in [19,20] to use active and passive methods for controlling separated flows on the aerodynamic surfaces of the blades.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%